PERENCANAAN DAN PERSIAPAN MENGHADAPI MASA PENSIUN - Siti Nurina Hakim (WARTA LPM, 2007)
his activity aims at proposing the contemplation and necessarytreatment to prepare workers in facing their retirement period so that theymay get rid of their anxiety which may disturb their life.  Therefore, themanagement of an institution should give necessary training for theirworkers to prepare their retirement period (MPP). This activity is conductedusing some methods as speech, discussion, and consultation. The solutionis taken from the participants since they are aware of their own needs, wants,abilities and obstacles. The solution from the participants is expected tobe conducted and applied easily, since they obviously tend to obey thecommitment created by them. After conducting this activity, there aresome significant changes in discourse from the participants in terms ofretirement condition, the next activities to be committed and how to starta new activity.